Kontribusi Industri Bambu di Kabupaten Gunungkidul bagi Sumber Penghidupan Para Petani dan Pengrajin - Marcellinus Mandira Budi Utomo (Jurnal Ilmu Kehutanan, 2021)
The bamboo industry has a role in the rural economy as a source of livelihood. This research has examined the contribution of bamboo as a raw material for farmers and as a bamboo product for artisan, from the perspective of direct use and income. Through a case study approach to the kitchen equipment industry in Rongkop and durable bamboo in Patuk, a value chain research framework was carried out. Field observations, semi-structured interviews with 40 respondents, and focus group discussions were conducted to obtain primary data, and supported by secondary data from government documents. An analysis of expenditure-income accompanied by a descriptive qualitative analysis is used to explain the practices of these two industries and determine the economic contribution of the bamboo industry to each bamboo farmer and artisan in each chain. The products produced by each actor are allocated more for trade than for domestic use. The economic contribution for bamboo farmers in the durable bamboo chain and kitchen utensils to monthly income above the poverty line ranges between 7,7% - 13,5% and 6,4% - 8,9%, respectively. The economic contribution for artisan in durable bamboo chain and kitchen utensils chain to monthly income above the poverty line ranged between 13,2% -104% and 152% -472% respectively. Only kitchen utensil artisans make their activities in these two chains as the main work, while the other actors do not because the income from their businesses is still incidental.